Solid-liquid extraction of daidzein and genistein from soybean: Kinetic modeling of influential factors. Issue 10 (26th November 2018) - Nan, Guanjun; Gao, Yuqiong; Guo, Liying; Meng, Xianxin; Yang, Guangde
Abstract: The extraction of daidzein and genistein from soybean has been studied and the kinetic modeling was established using four modeling equations. The goodness of fit was evaluated by statistical errors including the standard error of means (SEM), the adjusted correlation coefficient ( R 2 ), and chi-square ( χ 2 ). The best model was considered to be the So and Macdonald model and it could give the most adequate description of solid–liquid extraction of daidzein and genistein from soybean sample. The effect of process parameters on extraction yields of daidzein and genistein also has been investigated. The optimized extraction condition was at 333.2 K using 70% ethanol solvent at a solvent-to-solid ratio of 20 mL g −1 with an agitation speed of 300 rpm. The highest extraction yields of daidzein and genistein from soybean were 0.126 ± 0.006 and 0.184 ± 0.013 mg g −1, respectively. The activation energies for extraction kinetics of soybean were found to be 11.10 kJ mol −1 (washing step) and 13.96 kJ mol −1 (diffusion step) for daidzein, 10.47 kJ mol −1 (washing step) and 19.70 kJ mol −1 (diffusion step) for genistein, respectively.